IMPACT OF THE GROWTH ENHANCEMENT SUPPORT SCHEME (GESS) ON MAIZE FARMERS IN DUTSINMA LOCAL GOVERNMENT AREA OF KATSINA STATE, NIGERIA - Ibrahim, H. Y.; Ale-ojo, H. A.; Wahab, M. J. (FUDMA JOURNAL OF SCIENCES, 2023)
The study examined the impact of the Growth Enhancement Support Scheme (GESS) on maize farmers in Dutsin ma, Katsina state, Nigeria. Simple Random sampling was used to select 100 beneficiaries while purposive sampling was used to select100 non-beneficiaries of the scheme. Data were analyzed using descriptive and inferential statistics as well the Propensity Score Matching technique. The likelihood that a household selected at random will participate in the scheme was 66.7%. The likelihood of participation in the GESS increases with household size (p
Keywords: Impact, growth enhancement support scheme, maize farmers